Participation of women in the Malaysian parliament and the principles of shura' in Islamic law - Md. Sarkam, Mohd Kamarul Amree; Awang Hamat, Mohd Afandi (IIUM Press, International Islamic University Malaysia, 2017)
Malaysia is considered one of the most progressive countries in the Muslim world steadily moving towards enhanced political stability, general standard of living, technological advancement, and an integrated multi-cultural, multi-ethnic and multi-religious society. In fact, Malaysian women representatives contribute significantly in terms of insightful ideas, concrete arguments, and affirmative actions towards resolving national problems in general and women’s problems in particular. However, the participation of women in the Malaysian Parliament tends to remain undervalued and underappreciated by some factions in society who ascribe to women in general certain physical and intellectual weaknesses which render them unfit for such positions or even suppose that women should not be involved in public affairs at all and tend to their homes and families instead. Such negative preconceptions and stereotypes undermine the women’s dignity and continuously question their capability and thus reject the contributions of half of the populace towards achieving Malaysian excellence as a nation. This research discusses arguments for and against the participation of women in political affairs based on the primary and secondary sources of Islamic law with the aim to propose a moderate viewpoint and solution. A comparative study between the two institutions in general and women’s participation in particular provides the basis for a subsequent evaluation of existing shura' principles as to whether women should participate in the Malaysian Parliament or not.